Insecticides−Soil Microbiota Interactions - Maddela, Naga Raju (Springer International Publishing, 2018)
This book provides information about the nontarget nature of selected soil enzymes which are implicated in soil fertility and health and the methods for their assay. It also shows how these soil enzymes are affected by two different pesticides, buprofezin and acephate, used both extensively and intensively in modern agriculture. .